2015
DOI: 10.1007/s00125-015-3716-3
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean section per se does not increase the risk of offspring developing type 1 diabetes: a Swedish population-based study

Abstract: Aims/hypothesis Some studies have revealed a relationship between Caesarean section (CS) and type 1 diabetes, while other studies have not. By using the Swedish paediatric quality register we investigated whether birth by CS is related to the risk of developing type 1 diabetes during childhood.Methods All children diagnosed with type 1 diabetes from 2000 to 2012 and included in the register (n=9376) were matched with four controls by year, day of birth, sex and county of birth from the Swedish Medical Birth Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…The full text review excluded 71 articles, mostly because the association was not investigated (n = 64; these articles are listed in Appendix S1). A small number of articles (n = 7) were also excluded for various reasons, including studies that were restricted to the enrolment of participants with genetic susceptibility to type 1 diabetes (human leukocyte antigen [HLA]), studies in which the outcome was islet autoimmunity rather than T1DM, a study that only reported the risk of DM, a study in which the onset of T1DM was not reported, or one study that had overlap of the patient population with another included study . Finally, 21 articles were eligible for the final inclusion in the present meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full text review excluded 71 articles, mostly because the association was not investigated (n = 64; these articles are listed in Appendix S1). A small number of articles (n = 7) were also excluded for various reasons, including studies that were restricted to the enrolment of participants with genetic susceptibility to type 1 diabetes (human leukocyte antigen [HLA]), studies in which the outcome was islet autoimmunity rather than T1DM, a study that only reported the risk of DM, a study in which the onset of T1DM was not reported, or one study that had overlap of the patient population with another included study . Finally, 21 articles were eligible for the final inclusion in the present meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…was not reported, 37 or one study 38 that had overlap of the patient population with another included study. 19 Finally, 21 articles [18][19][20][21][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were eligible for the final inclusion in the present meta-analysis.…”
Section: Literature Review and Study Characteristicsmentioning
confidence: 99%
“…34 CS, and in particular elective CS has been associated with risk of CIDs in some studies, 22,24,27,32 but not all. 26,28,29 The hypothesis for the present study is that CIDs share a common aetiological component associated with being born by CS and that the risk is higher for elective than planned CS. The aim of the present study was to evaluate the risk of developing CIDs (including four common hospital-diagnosed childhood CIDs) after being born by caesarean delivery, taking advantage of the National Danish registries completeness, size, and long follow-up.…”
Section: Introductionmentioning
confidence: 90%
“…21 In contrast to planned CS (elective CS), acute CS will often be performed after initiation of the labour, where an open birth canal might potentially give access to the vaginal microbial community. Studies have addressed the risk of developing IBD, [22][23][24][25][26][27] DM, [27][28][29][30] CD, [31][32][33] and RA. 34 CS, and in particular elective CS has been associated with risk of CIDs in some studies, 22,24,27,32 but not all.…”
Section: Introductionmentioning
confidence: 99%
“…This question has also been debated in the pathogenesis of type 1 diabetes, where many studies have shown an increased risk of a child developing the disease if they were delivered by Caesarean section. However, a Swedish study has shown that this risk was only due to the fact that mothers with type 1 diabetes were more likely to have a baby by Caesarean section than mothers without the disease . Caesarean section per se did not increase the risk of a child developing type 1 diabetes and the risk of giving birth to a child who later developed type 1 diabetes was only increased if the mother had the disease herself.…”
mentioning
confidence: 97%